Lithocaldehydes A and B, polyketones from the deep sea-derived fungus Phomopsis lithocarpus FS508. Issue 37 (17th September 2020) - Liu, Huibo; Liu, Zhaoming; Li, Haohua; Tan, Haibo; Zhang, Qingbo; Li, Dongli; Liu, Hongxin; Zhang, Weimin
Abstract : Lithocaldehydes A (1 ) and B (2 ), a pair of novel diastereoisomers possessing an unprecedented 6/6/5/5/6 highly-fused ring system that forms an earring-like skeleton, were isolated from the deep sea-derived fungus, Phomopsis lithocarpus FS508. Abstract : Lithocaldehydes A (1 ) and B (2 ), a pair of novel diastereoisomers possessing an unprecedented 6/6/5/5/6 highly-fused ring system forming an earring-like skeleton, were isolated from the deep sea-derived fungus Phomopsis lithocarpus FS508. The structures of 1 and 2 were fully characterized and established through extensive spectroscopic interpretations and ECD calculations. Moreover, compounds 1 and 2 were shown to be promising antibiotics, exhibiting potent antifungal activities that are comparable to those of the positive control nystatin.